ANALISIS KELAYAKAN FINANSIAL USAHA TORTILA IKAN TUNA PADA INDUSTRI RISQA MULIA DI DESA OLAYA KECAMATAN PARIGI KABUPATEN PARIGI MOUTONG - Nilam, Nilam; Lamusa, Arifuddin; Laapo, Alimuddin (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study aimed to evaluate the financial feasibility of the tuna tortilla chip business at Risqa Mulia Industry in Olaya Village, Parigi Subdistrict, Parigi Moutong Regency, using Net Present Value (NPV), Net B/C Ratio, Internal Rate of Return (IRR), and Payback Period criteria. The research was conducted from July to August 2019. Respondents were selected purposively, consisting of three internal company members: the company leader, treasurer, and a production employee. Financial feasibility analysis was used as the method for data analysis. The results indicate that the tuna tortilla chip business at Risqa Mulia Industry is financially feasible based on the assessment criteria. The calculations yielded an NPV of IDR 72,890,925, a Net B/C Ratio of 2.93, an IRR of 42.96%, which exceeds the initial interest rate, and a Payback Period of 2 years and 5 months, achieved before the end of the business period.